Critical of the Use of Constitutional Court Decisions by Constitutional Enforcers and Political Tools by the Power Elite - Jenda Ingan Mahuli (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to critically analyze the position and role of the Indonesian Constitutional Court (MK) in maintaining constitutional supremacy amidst the dynamics of national politics. The purpose of this study is to critically analyze the use of Constitutional Court decisions in Indonesian constitutional practice, by examining the shift in the function of decisions from an instrument for enforcing the constitution to a tool for political legitimacy by the power elite. This study uses a descriptive qualitative approach with document analysis methods, in-depth interviews with constitutional law experts, and critical reviews of MK decisions considered to be politically charged. The results of the study indicate that there is a tendency for the power elite to utilize MK decisions as an instrument of political legitimacy. The contributing factors include the judge recruitment process that is still strongly influenced by political nuances, weak internal ethical mechanisms, and external pressures from the dynamics of executive and legislative power. The novelty of this study lies in its critical-interdisciplinary approach that examines Constitutional Court decisions not only as normative legal products, but also as political instruments mobilized by the power elite. This study emphasizes that the independence of the MK is the main foundation of a democratic rule of law. Therefore, institutional reform and strengthening of constitutional judicial ethics are needed so that the Constitutional Court does not get caught up in the vortex of practical political interests, but instead consistently becomes the guardian of the constitution and protector of constitutional justice for all Indonesian people.